2011
DOI: 10.1042/bj20101500
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β2 promotes Snail-mediated endothelial–mesenchymal transition through convergence of Smad-dependent and Smad-independent signalling

Abstract: SYNOPSIS Endothelial-mesenchymal transition (EndMT) is a critical process of cardiac development and disease progression. However, little is know about the signaling mechanisms that cause endothelial cells to transform into mesenchymal cells. Here we show that transforming growth factor-beta2 (TGF-β2) stimulates EndMT through Smad, MEK, PI3K, and p38 MAPK signaling pathways. Inhibitors of these pathways prevent TGF-β2-induced EndMT. Furthermore, we show that all of these pathways are essential for increasing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
257
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(274 citation statements)
references
References 33 publications
(33 reference statements)
10
257
0
3
Order By: Relevance
“…These data indicate that active endothelial TGFβ signaling through ALK5 and the Smad2 and Smad3 transcription factors is associated with EndMT and confirms previous data reported by us and others (Kokudo et al, 2008;Krenning et al, 2008;Moonen et al, 2010;Medici et al, 2010Medici et al, , 2011Yoshida et al, 2012).…”
Section: Tgfβ1 Induces Endothelial-mesenchymal Transition In An Alk5-supporting
confidence: 81%
“…These data indicate that active endothelial TGFβ signaling through ALK5 and the Smad2 and Smad3 transcription factors is associated with EndMT and confirms previous data reported by us and others (Kokudo et al, 2008;Krenning et al, 2008;Moonen et al, 2010;Medici et al, 2010Medici et al, , 2011Yoshida et al, 2012).…”
Section: Tgfβ1 Induces Endothelial-mesenchymal Transition In An Alk5-supporting
confidence: 81%
“…The development of EndMT is abolished by use of a p38 MAPK inhibitor. EndMT induction via the overexpression of HD3-␣ or by direct stimulation with cytokines is decreased in the presence of a p38 MAPK inhibitor, suggesting that p38 MAPK is involved in EndMT (14,28). Additionally, it has been reported that p38 MAPK activation plays an important role in TGF-␤ intracellular signaling, promoting fibrotic actions (21,29).…”
Section: Discussionmentioning
confidence: 95%
“…(vi) Furthermore, we used RT-qPCR and protein detection by western blot to demonstrate that H 2 O 2 induces the expression and secretion of TGF-b1 and TGF-b2, and it has been clearly demonstrated that TGF-b1 and TGF-b2 induce the conversion of ECs into myofibroblasts. 19,34,35,40,41,85 expression by converting them from normal to pathological. This information will be useful in designing new and improved therapeutic strategies against oxidative stressmediated systemic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proteins that constitute the extracellular matrix (ECM), including fibronectin (FN), collagen type I and III, and vimentin are increased. [19][20][21][22] TGF-b binds its plasma membrane receptor, activin receptor-like kinase 5 (ALK5), to activate it and subsequently elicit intracellular signaling. 23,24 Several proteins that are involved in TGF-b intracellular signaling include the canonical pathway of phosphorylation of the family of Smad proteins and non-canonical intracellular pathways, to perform the activation of nuclear factor-kappa B (NF-kB).…”
mentioning
confidence: 99%